The restaurant sector faced with Covid-19 pandemic: Evidence from Italy - Fellini, Ivana; Fullin, Giovanna; Gaspani, Fabio (Communitas)

(untitled) (UQÀM Département des sciences juridiques, 2024)
Italy has been one of the European countries most severely affected by the Covid-19 pandemic, with dramatic economic impacts on the service sector. On the basis of a quantitative and qualitative analysis, this article analyses the impact of the pandemic on the Italian restaurant industry by taking into consideration the perspective of both employers and employees. Specifically, the article focuses, on the one hand, on the working conditions and job quality in the sector; on the other hand, on the changes occurred in the restaurant industry, the impact of policies implemented during the health emergency and the problem of labour shortages.